Activity of 3, 19-isopropylidinyl andrographolide against herpes simplex virus type 1 in an animal model. (April 2022) - Chuerduangphui, Jureeporn; Nukpook, Thawaree; Pientong, Chamsai; Aromdee, Chantana; Suebsasana, Supawadee; Khunkitti, Watcharee; So-in, Charinya; Proyrungroj, Kanisara; Ekalaksananan, Tipaya
Background: In our previous study, the semi-synthetic analog of andrographolide, 3, 19-isopropylideneandrographolide (IPAD), acts more effectively against herpes simplex virus (HSV) infection in cell culture than does acyclovir. IPAD inhibits cytopathic effect and production of HSV wild types and drug-resistant strains. Its effect is associated with the reduction of immediate-early regulatory protein (ICP27) and early proteins (ICP8 and UL42), indicating a mode of action different from that of acyclovir. Therefore, studies of the anti-HSV activity of IPAD in animal models are required before further application. Material & Method: Prednisolone-treated BALB/c mice were cutaneously infected with HSV-1 wild-type KOS strain. Experimental groups included control groups (untreated or treated only with the cream base) and treatment groups (with acyclovir or IPAD creams). Creams were applied four times daily for 10 days after infection to the relevant groups. The skin lesion score was assessed twice a day for 10 days. In addition, the effect of IPAD on HSV copy number and HSV late gene (gD) expression was investigated in skin lesion cells by quantitative real-time polymerase chain reaction. Result: IPAD cream was significantly effective in delaying the development of skin lesions and regression of the skin lesion score by day 5 (P < 0.01) compared with untreated controls. In addition, this IPAD cream significantly reduced HSV DNA copy number and gD gene expression (P < 0.01). No signs of irritation were observed at the application site. Conclusion: Topical administration of IPAD cream reduced skin lesions in mice cutaneously infected with HSV-1 KOS.